Surveillance of enteric viruses in environmental waters from Hurlingham - Vitali, Franco Sergio; Frydman, Camila Ayelén; Dus Santos, María José; Mozgovoj, Marina Valeria (Mae Fah Luang University. School od Agro-Industry, 2023)
Enteric viruses are excreted in the feces of infected individuals and are introduced into environmental waters through the discharge of treated and untreated wastewater. Surveillance of enteric viruses in surface waters can provide information regarding viral circulation in a community. The aim of this work was to detect Adenovirus (AdV), Rotavirus (RV), Norovirus GI (NoV GI), Norovirus GII (NoV GII), Hepatitis A (HAV) and Hepatitis E (HEV) in stream waters from the Arroyo Soto, which is located in the northwest of the Metropolitan area of Buenos Aires, Argentina, and to genetically characterize the detected strains.Methods: A total of 45 samples were collected at five points along the stream located at Hurlingham City, Buenos Aires, from January to July 2023. Samples were analyzed by real-time PCR for the detection of enteric viruses, after a concentration step. Positive samples were subjected to end point PCR for subsequent sequencing.Results: Globally, the percentage of positive samples was 4 % for HEV, 40 % for RVA, 27 % for NoV GII, 2 % for NoV GI, 2 % for HAV and 84 % for AdV. 44 % of the samples were positive for at least two viruses. RVA showed a higher detection in winter months, while AdV was detected during the whole period. A fragment of HAV 5´UTR from the positive sample was sequenced and the phylogenetic analysis revealed that the detected strain belonged to genotype IA.Conclusion: Results shown demonstrate that water surveillance could help to identify circulating strains in a population complementing health care services to prevent potential viral outbreaks. Moreover, it reinforces the importance of environmental surveillance as a key tool for pollution control and human risk exposure.
Keywords: Ciencias Exactas y Naturales